PEMANTAUAN BERBASIS ELEKTRONIK (MEDICATION EVENT MONITORING SYSTEM (MEMS)) UNTUK MENINGKATKAN KEPATUHAN TERHADAP TERAPI ANTIRETROVIRAL PADA ANAK DENGAN INFEKSI HIV/AIDS: TINJAUAN SISTEMATIS - Amelia Hartika Rani; Dwi Budiyati; Rinezia Rinza Farizal; Nyimas Heny Purwati; Irna Nursanti (PT.Mantaya Idea Batara, 2025)
Tuberculosis is still the main cause of death due to infectious diseases throughout the world. Adherence to antiretroviral (ARV) treatment for HIV infection is a major challenge because it involves many factors. This systematic review follows the PRISMA guidelines checklist and includes articles from various databases, such as Pubmed, Cochrane and Proquest. Quality assessment of each article is carried out using the Critical Appraisal Skills Program (CASP). The search was carried out using the keywords